Food chain information in the European pork industry: Where are we?. (December 2021) - Bonardi, Silvia; Blagojevic, Bojan; Belluco, Simone; Roasto, Mati; Gomes-Neves, Eduarda; Vågsholm, Ivar
Abstract: Background: The European General Food Law (Regulation No 178/2002) declares that risk analysis should be the basis of food legislation to achieve a high level of protection of human health. Concerning meat safety, the food chain information (FCI) set down by Regulation No 853/2004 is a very important tool that is required for animals admitted to slaughter. To properly integrate FCI, harmonised epidemiological indicators (HEIs) have been proposed by EFSA for high priority risks and risks that might emerge in the future. Scope and approach: In the pig meat chain, the HEIs within meat inspection cover Salmonella spp., Yersinia enterocolitica, Toxoplasma gondii, Trichinella spp., Taenia solium and mycobacteria. Nevertheless, ten years after the HEIs specification were published, only two biological hazards ( Trichinella and Salmonella ) are included in official control programs in the EU countries. While Trichinella monitoring is mandatory, Salmonella control plans have been implemented by some countries only. Key findings and conclusions: In countries where Salmonella in pigs is monitored at farm level, the status of the farm is described in the FCI. This information is crucial for the risk manager to organise slaughter operations and implement hygienic measures, as well as for the competent authorities to properly follow inspection procedures and additional controls according to Regulation No 2019/627. Since FCI needs to enable forward and backward flow of information on animal and public health hazards between all operators involved in pig husbandry and pig meat production, its implementation with HEIs will allow risk-based decision making in food safety. Highlights: Harmonised Epidemiological Indicators (HEIs) in pigs were suggested by EFSA in 2011. The HEIs on farms should integrate Food Chain Information (FCI) of slaughtered pigs. Trichinella monitoring is mandatory in all EU countries. Salmonella control plans are implemented in some EU countries only. FCI is still lacking important information on animal health status on farms.